Mecanismos de transdução de sinal envolvidos com a diferenciação de osteoblastos e osteocitos - Zambuzzi, Willian Fernando, 1980- (2008)
Orientadores: Carmen Verissima Ferreira, Jose Mauro Granjeiro, Maikel Peppelenbosch